تقييم التغير اللوني لأنواع جديدة من الكمبوزت ضمن محلول الشاي (دراسة مخبرية) - عبود, سعاد; ونوس, محمد (Latakia University Journal -Medical Sciences Series, 2019)
Aim of the study:to evaluate colorsability of several composite resins in tea Methods and materials: the sample consist of 30 discs of (admira fusion voco , tetric evoceram vivadet ivoclar , tetric N-ceram vivadent ivoclar) devided into three group (A ,B, C) each group consist of Ten randomly selected discs of each material. Samples were immersed in tea . The color was recorded after 1, 7, and 30 days of immersion using easy shade device .. The data were analyzed based on the one way anova test. Results: After 1 day of immersion,there was no significant difference between the samples.but admira fusion showed significantly less discoloration than tetric evoceram and tetric N-ceram after 7 and 30 days. الهدف :يهدف هذا البحث إلى تقييم الثبات اللوني لعدة أنواع مختلفة من الكمبوزت عند غمرها ضمن الشاي. المواد والطرق : تألفت العينة من 30قرصاً من المواد التالية admira fusion voco , tetric evoceram vivadent ivoclar , tetric N-ceram vivadent ivoclar)) وزعت على ثلاث مجموعات(A,B,C)، تألفت كل مجموعة من 10 أقراص, غمرت العينة ضمن أوعية تحوي على الشاي, ثم رفعت بعد 24 ساعة لتقييم التغير اللوني باستخدام جهاز easy shade ، ثم أعيدت للمحاليل لتكرار التقييم بعد فترة أسبوع ثم بعد فترة شهر. ليتم استخلاص النتائج و حللت البيانات باستخدم برنامج SBSS وفق اختبار التباين ANOVA. النتائج: أظهرت نتائج البحث أنه لا توجد فروق دالة إحصائياً بعد فترة 24 ساعة بينما كانت الفروق ذات دلالة احصائية بعد أسبوع و بعد شهر,حيث أظهر كمبوزت admira fusionتغيرا لونيا أقل بشكل ملحوظ من كل من tetricevoceram و tetric N-ceram.